The matrilineal system of the Minangkabau and its persistence throughout history: a structural perspective - Alexander Stark (Vol 13, 2013, pp 1–13, 2013)
The matrilineal society of the Minangkabau has fascinated numerous researchers from around the world. The co-existence of a matrilineal family structure and system of inheritance on one side and an Islamic way of life on the other side has intrigued these researchers. However most of the research has been descriptive or focused on a special element of the Minangkabau way of life. Two outstanding researchers namely Taufik Abdullah and Frederick Errington tried to offer theoretical approaches, and this paper will examine these approaches. Moreover it will also attempt to look at the historical developments from a structural point of view. It will be argued that the historical development and its structural analysis will help to understand the society in West Sumatra. Such a structural perspective could also be useful for the research of other societies in order to understand the inherent elements of a specific culture.